2013
DOI: 10.1148/radiol.12121374
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Weight Estimation: Comparison of Two-dimensional US and MR Imaging Assessments

Abstract: In the second half of pregnancy, fetal density varies with gestational age. Fetal weight estimates by using fetal MR imaging are better than those by using prenatal US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 32 publications
5
49
0
3
Order By: Relevance
“…Among clinical methods in our study, Dares formula was 100% sensitive in predicting weight >3.5 Kg Kacem et al used MRI to predict EBW and found it more accurate then USG however it cannot be routinely used. 5 In our study we found Johnson equation giving a fair degree of accuracy compared to ultrasonic methods which had lower error at extremes of fetal weight. Obstetrical equation did not give good accuracy; however Shittu et al found it quite accurate in a study conducted in Nigeria.…”
Section: Discussionmentioning
confidence: 48%
“…Among clinical methods in our study, Dares formula was 100% sensitive in predicting weight >3.5 Kg Kacem et al used MRI to predict EBW and found it more accurate then USG however it cannot be routinely used. 5 In our study we found Johnson equation giving a fair degree of accuracy compared to ultrasonic methods which had lower error at extremes of fetal weight. Obstetrical equation did not give good accuracy; however Shittu et al found it quite accurate in a study conducted in Nigeria.…”
Section: Discussionmentioning
confidence: 48%
“…Whether this is due to a different density in such fetuses, indicating a need for a customized formula in MR-EFW, is unknown. In a previous study, the density of fetuses did not differ between diabetic and nondiabetic mothers, but the study was underpowered to show such a difference [14] .…”
Section: Discussionmentioning
confidence: 84%
“…Further, all planimetric measurements were performed by maternal-fetal medicine trainees supervised by C.K. on picture archiving and communication system (PACS; Impax, Agfa-Gevaert, Mortsel, Belgium) as previously described [14] .…”
Section: Mr Imaging Planimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…2.6% for MR-EFW and 6.4% for US-EFW [15] . Fetal weight in 26.6% of cases was estimated with an error of more than 10% using US and 1.1% with MR imaging.…”
Section: Introductionmentioning
confidence: 88%